A case of primary breast diffuse large B cell lymphoma - Huy, Trinh Le; Anh , Tran Dinh (Tạp chí Nghiên cứu Y học, 2021)
Primary breast diffuse large B-cell lymphoma (DLBCL) is a rare non-Hodgkin’s lymphoma with limited data. We here report a case of primary breast diffuse large B-cell lymphoma mimicking breast cancer. A 52-year-old woman had a painless mass in her right breast. Fine needle aspiration cytology and core biopsy were performed which suggested malignant features but could not confirm the specific subtype. Excisional biopsy then was conducted revealing non-Hodgkin lymphoma, which was subsequently confirmed with histopathology and diagnosed as diffuse large B-cell lymphoma (DLBCL). A chest computed tomography scan revealed a 3.5 cm sized breast mass with skin thickening and modest lymphadenopathy in the ipsilateral axilla. The patient received six courses of R-CHOP (cyclophosphamide, doxorubicin, vincristine, and prednisolone plus rituximab) chemotherapy, then whole breast radiation (30Gy in 15 fractions). At 12 months of follow-up, the patient survives with no evidence of disease. No morbidities occurred in this patient during the follow-up period. We briefly review the current practice pattern in patients with primary breast diffuse large B-cell lymphoma.